Does the COVID-19 Pandemic Improve Global Air Quality? New Cross-national Evidence on Its Unintended Consequences - Hai-Anh H. Dang; Trong-Anh Trinh (Global Labor Organization (GLO), 2020)
Despite a growing literature on the impacts of the COVID-19 pandemic, scant evidence currently exists on its impacts on air quality. We offer the first study that provides cross-national evidence on the causal impacts of COVID-19 on air pollution. We assemble a rich database consisting of daily, sub-national level data of air quality for 178 countries before and after the COVID-19 lockdowns, and investigate their impacts on air quality using a Regression Discontinuity Design approach. We find the lockdowns to result in significant decreases in global air pollution. These results are consistent across measures of air quality and data sources and robust to various model specifications. Some limited evidence emerges that countries with a higher share of trade and manufacturing in the economy or with an initially lower level of air pollution witness more reduced air pollution after the lockdowns; but the opposite result holds for countries near the equator. We also find that mobility restrictions following the lockdowns are a possible explanation for improved air quality.
Keywords: D00; H00; O13; Q50; 330; COVID-19; air pollution; mobility restriction; RDD